Habitat selection by marine larvae in changing chemical environments. Issue 1 (15th January 2017) - Lecchini, D.; Dixson, D.L.; Lecellier, G.; Roux, N.; Frédérich, B.; Besson, M.; Tanaka, Y.; Banaigs, B.; Nakamura, Y.
Abstract: The replenishment and persistence of marine species is contingent on dispersing larvae locating suitable habitat and surviving to a reproductive stage. Pelagic larvae rely on environmental cues to make behavioural decisions with chemical information being important for habitat selection at settlement. We explored the sensory world of crustaceans and fishes focusing on the impact anthropogenic alterations (ocean acidification, red soil, pesticide) have on conspecific chemical signals used by larvae for habitat selection. Crustacean ( Stenopus hispidus ) and fish ( Chromis viridis ) larvae recognized their conspecifics via chemical signals under control conditions. In the presence of acidified water, red soil or pesticide, the ability of larvae to chemically recognize conspecific cues was altered. Our study highlights that recruitment potential on coral reefs may decrease due to anthropogenic stressors. If so, populations of fishes and crustaceans will continue their rapid decline; larval recruitment will not replace and sustain the adult populations on degraded reefs. Highlights: both crustacean and fish larvae chemically are attracted to chemical cues produced by conspecifics in acidified water, soil or pesticide pollution, the larval ability to recognized conspecifics chemically was altered exposure to chlorpyrifos had lasting effects on larvae, while other anthropogenic induced changes only altered behaviour the conspecific fingerprints were modified in polluted water with the appearance of some alarm peaks